A deep search for C2H in the oxygen-rich post-AGB star OH 231.8+4.2 - Yang, Jianchao; Yang, Xiaofeng; Zhu, Cheng (Frontiers in Astronomy and Space Sciences, 2024)
In carbon-rich environment, C2H emission is seen to be associated with HC3N, but whether it can trace the HC3N molecule in oxygen-rich environment is unknown. Here, we have searched for rotational emission from ethynyl radical (C2H) in the oxygen-rich circumstellar envelope (CSE) of the post-asymptotic giant branch (post-AGB) star OH 231.8+4.2, a renowned galactic proto-planetary nebula (PPN) known to display cyanoacetylene (HC3N) emission. Our observations were conducted using the James Clerk Maxwell Telescope (JCMT), and the total on-source time is 11.9 h. Base on local thermodynamic equilibrium (LTE) excitation analysis, we have calculated the column density and the abundance relative to H2 for C2H. The calculated column density for C2H is less than 1.4 × 1013 cm-2, which corresponds to a fractional abundance, f (C2H), less than 4.5 × 10–9. This inference suggests that the typical transformation pathway from C2H and C2H2 to HC3N may not play a significant role in O-rich environments. It indicates the presence of alternative, unidentified pathways that contribute to the formation of HC3N in O-rich circumstellar envelopes.